Margin Pembiayaan Sistem Murabaha di Bank-Bank Umum Syariah dan Pengaruhnya terhadap Keputusan Nasabah Pensiunan - Muhdar HM Muhdar HM (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
The phenomenon of retirement customers' decision to take over debts from conventional financial institutions to Islamic finance continues to increase, indicating a change in customer paradigm, predicted due to several factors including financing margin factors. This article explains the extent to which financing margins affect the decision of retired customers to take over from conventional banks to Islamic banking. This study uses a quantitative method with an analysis unit of 161 retired clients who have filled the questionnaire with multi-stage sampling. The results of the study show that murabaha financing margins have a positive and significant effect on the decision making of retired customers in the taking over of financing. This means that good financing margins have great potential to bring retired customers from conventional banks. Thus, this result has implications for marketers and policy makers that retired customers decide based on potential financing products.